Mechanical Behavior of Buried Pipelines Subjected to Faults - Xiaolong Wei; Wenshuai Jiao; Xi Zeng; Danfu Zhang; Guofeng Du (Advances in Civil Engineering)
The length of buried pipelines usually extends thousands of meters or more in engineering, and it is difficult to carry out full-scale tests in the laboratory. Therefore, considering the seriousness of pipeline damage and the difficulty of operating tests and other test limitations, it is necessary to develop a reasonable method to simplify the length of the model for a practical lab test. In this research, an equivalent spring model was established to simulate the small deformation section of the pipeline far away from the fault and the effect of fault displacements, pipeline diameters, wall thicknesses, buried depths, soil materials, and spring constraints on the mechanical properties of pipelines was analyzed. Based on the finite element model using ABAQUS software, the results of the shell model with fixed boundary at both ends were compared; in addition, the dynamic effect of pipelines was investigated. The results show that the two-end spring device can better control the size of the test model and enhance the reliability of the test results. The vibration response of the pipeline mainly depends on the inconsistent movement of soil at both ends of the fault. The analysis results show that choosing a larger pipeline diameter, smaller buried depth, noncohesive backfill soil, and spring with a smaller elastic coefficient is beneficial to reduce pipeline strain and resist pipeline deformation. A simplified formula of the axial compressive strain of buried pipelines across oblique-slip fault is obtained.